Efficacy of aromatherapy for reducing pain during labor: a randomized controlled trial - Rajavadi Tanvisut (2018)
© 2018, Springer-Verlag GmbH Germany, part of Springer Nature. Background: Many strategies for labor pain management have been studied, including aromatherapy, which is a noninvasive, alternative medicine used as an adjunct for labor pain control. Nevertheless, the results were contradictory. Therefore, we conducted this study to determine the effectiveness of aromatherapy for reducing pain during labor. Methods: A randomized controlled trial was carried out on Thai laboring primigravidae who were a low-risk singleton pregnancy undergoing vaginal delivery. All participants, both study and control group, received standard obstetric care. Aromatherapy was only provided to the study group during the first stage of labor. The women rated their pain intensity by rating scales at different stages of labor. The primary outcome was pain scores and the secondary outcomes were necessity of painkiller usage, labor time, aromatherapy-associated complications, route of delivery, and Apgar scores. Results: A total of 104 women were recruited, 52 in each group. Baseline characteristics and baseline pain scores were comparable. The median pain score of latent and early active phase was lower in the aromatherapy group, 5 vs 6 and 7 vs 8, respectively. The mean differences of pain scores between latent and early active phase and the baseline were significantly lower in the aromatherapy group, 1.88 vs 2.6 (p = 0.010) and 3.82 vs 4.39 (p = 0.031), respectively. Late active phase pain scores and other perinatal outcomes were not significantly different. Conclusion: Aromatherapy is helpful in reducing pain in latent and early active phase, and can probably be used as an adjunctive method for labor pain control without serious side effects.